How brain and neuronal networks explain human reality - Monserrat, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
How is human reality presented to us in phenomenological experience? It is the one we see daily in our personal and social life. We are made of matter, we are part of the evolutionary universe. In addition, a psychic life is formed in us: sensation, a system of perceptions, an integrated consciousness, a condition of psychological subject; We produce knowledge, emotions, motivations; But, above all, we have a mind that rationally moves and installs us into a world of human emotions; This emotional reason lies at the base of the search for the truth of the universe, the meaning of life and the moral responsibility, in personal and social life. Our human reality is, therefore, a personal reality. We are persons. Now, how does science, neurology, explain today the fact that our human reality possesses these properties that give us the personal condition? This should be able to be explained (this is the initial assumption) from the physical-biological world. Now, in particular, how does science make it possible to explain that evolution has produced us in our condition of ratio-emotional persons? That is, what is the physical support that makes intelligible the psycho-bio-physical ontology that evolutionarily produces our personal phenomenological experience? This is, ultimately, still the fundamental question of human sciences. What science, namely neurology, must explain (that is, know the causes that have produced it) is obvious: the fact of our sensibility-consciousness, our condition of psychic subjects, knowledge and emotional reason that have emerged in the universe; In such a way that, once the emotional reason emerges, it leads by itself to constitute the rational activity and the emotions of the human person aimed at building the meaning of his life. These are the issues we address in this article.
Keywords: science; neurology; sensitivity-awareness; subject; memory; emotional; moral; person; brain; neural networks.